Pengaruh Latihan Kekuatan Otot Lengan Terhadap Keterampilan Passing Bawah Pada Permainan Bola Voly Siswa Putra Kelas Atas SDN Maubeli Kabupaten Timor Tengah Utara - Rosari, Ermy Tresilda De; Talan, Rudobertus; Wora, Dionisius; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effect of arm muscle strength training on underarm passing skills in volleyball for upper-grade male students at Maubeli Elementary School, North Central Timor Regency. The study used a quantitative approach with a one-group pretest–posttest design. The population and sample size were 20 students (total sampling). The treatment, arm muscle strength training, was given in a structured manner over five sessions. Data analysis included descriptive statistics, residual normality tests, and simple linear regression. The results showed a correlation coefficient (R) of 0.458 and a determination coefficient (R²) of 0.210, indicating that 21.0% of the variation in underarm passing skills was influenced by arm muscle strength. The ANOVA test showed F count = 4.774 with Sig. = 0.042 (<0.05), indicating that arm muscle strength training significantly influenced underarm passing skills. The regression equation obtained was Y = 0.080 + 0.683X. These findings confirm that an arm muscle strength training program can be used as a physical education (PJOK) learning strategy to improve the quality of basic volleyball underarm passing techniques in elementary school students. Keywords: Arm muscles, strength training, underhand passing, volleyball, elementary school students